Genetic diversity in 96 accessions of cassava as revealed by Random Amplified Polymorphic DNAs (RAPDs) - Offei, Samuel Kwame; Danquah, E.Y.; Okai, E.; Mignouna, Hodeba D.; Dixon, Alfred G.O. (2004)
Some 96 accessions of cassava (Manihot esculenta) were evaluted for genetic diversity using random amplified polymorphic DNA (RAPD) primers. Ten out of 80 Primers were considered highly informative and were used to fingerprint all of the accessions. Amplification of genomic DNA with the primers revealed a total of 63 different banding positions ranging from 0.3 to 2.0 kb. The number of bands per primer ranged from five to nine. The RAPD patterns were highly reproducible. While no variation was observed among plants belonging to the same accession, a large number of inter-accession polymorphisms enable us to reliably discriminate between all of the accessions.